Effective Technologies For Forming A Sense Of Responsibility In Preschool Children - Xojamiyarov S. (Euro Asian Journal Publishing, 2025)
The organization of the pedagogical process based on innovative educational technologies in the formation of a sense of responsibility among preschoolers has been confirmed in a well-founded experiment-approbation. Technology is not useful only for developing educational content, but also for comprehensive parenting. The article highlights the methodology of using TRIZ technology in order to form a sense of responsibility among preschoolers using a number of teaching methods and technologies
Keywords: Technology; activity; fairy tale; story